Perancangan dan Pembangunan Aplikasi E-Commerce Berbasis Mobile TechTrove - Rahman, Saifulloh; Arimogi, I Komang (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
This paper presents the design and development of mobile-based e-commerce applications specifically designed for electronic devices. With the growing popularity of smartphones and growing demand for online shopping, the need for a user-friendly and efficient mobile e-commerce application has become imperative. The proposed application aims to provide a seamless shopping experience for users who wish to purchase electronic devices through their mobile devices. The design process covers multiple aspects, including user interface design, navigation flows, and integration of important ecommerce features such as product listings, filtering, and secure payment methods. The development phase involves implementing the design using the appropriate programming languages ??and frameworks to ensure compatibility across various mobile platforms. The app's success will be evaluated based on user feedback, performance metrics, and its ability to improve the overall shopping experience for electronics enthusiasts. By combining mobile technology and e-commerce, this research contributes to the advancement of the digital shopping landscape and offers a convenient platform for users to easily browse and buy electronic devices.